Pressure-induced stiffness of Au nanoparticles to 71 GPa under quasi-hydrostatic loading. (16th November 2015) - Hong, Xinguo; Duffy, Thomas S; Ehm, Lars; Weidner, Donald J
Abstract: The compressibility of nanocrystalline gold (n-Au, 20 nm) has been studied by x-ray total scattering using high-energy monochromatic x-rays in the diamond anvil cell under quasi-hydrostatic conditions up to 71 GPa. The bulk modulus, K 0, of the n-Au obtained from fitting to a Vinet equation of state is ~196(3) GPa, which is about 17% higher than for the corresponding bulk materials ( K 0 : 167 GPa). At low pressures (<7 GPa), the compression behavior of n-Au shows little difference from that of bulk Au. With increasing pressure, the compressive behavior of n-Au gradually deviates from the equation of state (EOS) of bulk gold. Analysis of the pair distribution function, peak broadening and Rietveld refinement reveals that the microstructure of n-Au is nearly a single-grain/domain at ambient conditions, but undergoes substantial pressure-induced reduction in grain size until 10 GPa. The results indicate that the nature of the internal microstructure in n-Au is associated with the observed EOS difference from bulk Au at high pressure. Full-pattern analysis confirms that significant changes in grain size, stacking faults, grain orientation and texture occur in n-Au at high pressure. We have observed direct experimental evidence of a transition in compressional mechanism for n-Au at ~20 GPa, i.e. from a deformation dominated by nucleation and motion of lattice dislocations (dislocation-mediated) to a prominent grain boundary mediated response to external pressure. The internal microstructure inside the nanoparticle (nanocrystallinity) plays a critical role for the macro-mechanical properties of nano-Au.